(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
The deaths due to plastic bag asphyxia/suffocation uncommon among older people. Plastic bag asphyxia deaths commonly occur as accidental deaths in solvent abusers among adolescents and in autoerotic asphyxia among adults. Many suicides by plastic bag asphyxia were reported in the elderly, chronically, and terminally ill patients. The suicidal plastic bag asphyxia deaths were increasing due to the ready availability of asphyxia steps in the published books and the Internet. We are presenting a case of suicidal plastic bag asphyxia death in a 43- year-old woman. She was found unconscious in the bathroom was taken to hospital and declared brought dead. Autopsy findings were cyanosis of lips and nailbeds, petechial hemorrhages in the epiglottis and congestion of internal organs. The deceased used a scarf to fasten the plastic bag around the neck and no other evidence was found at the crime scene. The woman’s death was suicidal by plastic bag asphyxia.